2021
DOI: 10.1155/2021/9155861
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Transformation and Corporate Total Factor Productivity: Empirical Evidence Based on Listed Enterprises

Abstract: This paper mainly attempts to disclose the action mechanism of corporate digital transformation on total factor productivity (TFP). Based on the data on listed enterprises in 2007–2019, the influence of corporate digital transformation on TFP was analyzed empirically. The results show that corporate digital transformation can significantly promote TFP. Heterogeneity analysis reveals that the promoting effect of digital transformation on TFP only exists in small and medium high-tech enterprises, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Some findings show that digital transformation has improved the total factor productivity of enterprises by driving enterprise innovation, human capital structure, deep integration of the manufacturing industry and modern service industry, and enterprise operation levels [8]. And in the process of digital transformation, firms have improved their management efficiency and technical level so as to improve their productivity [9]. Moreover, digital transformation reduces the external transaction costs faced by firms, effectively promotes the level of the professional division of labor, and improves the productivity of enterprises [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some findings show that digital transformation has improved the total factor productivity of enterprises by driving enterprise innovation, human capital structure, deep integration of the manufacturing industry and modern service industry, and enterprise operation levels [8]. And in the process of digital transformation, firms have improved their management efficiency and technical level so as to improve their productivity [9]. Moreover, digital transformation reduces the external transaction costs faced by firms, effectively promotes the level of the professional division of labor, and improves the productivity of enterprises [10].…”
Section: Introductionmentioning
confidence: 99%
“…This transformation affects different levels and steps of output creation in companies, including the way firms interact with consumers and the way they do business (Kretschmer & Khashabi, 2020). The existing studies have shown that corporate digital transformation helps to reduce corporate costs, increase corporate manage-ment efficiency, and promote corporate technological progress (Zeng & Lei, 2021). In this context, it is of great academic value and practical significance to discuss the economic consequences of digital transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is of great academic value and practical significance to discuss the economic consequences of digital transformation. At present, scholars have studied the economic consequences of digital transformation on corporate performance, total factor productivity, merge and acquisitions, international strategy and other aspects (Zeng & Lei, 2021;Chen & Hao, 2022;Gao et al, 2022), but less attention is paid to the impact of enterprise digital transformation on financing costs.…”
Section: Introductionmentioning
confidence: 99%
“…is mathematical model can minimize the risk of enterprise digital transformation failure. Zeng et al, [18] used the company's listing development data for many years to study the relationship between the digital transformation of enterprises and the mechanism of action. e results of the study show that the digital transformation of enterprises can promote the improvement of factor productivity.…”
Section: Related Workmentioning
confidence: 99%